Impact of a sport-specific nutrition education program on knowledge and eating disorder risk in youth competitive climbers: a pilot study - Quesada, A.; Pablos, A.; Drehmer, E. (Frontiers in Nutrition, 2026)
Introduction: Sport climbing has gained popularity among youth athletes, raising concerns about eating disorders (ED) and relative energy deficiency in sport (RED-S). Although nutritional education has shown promise in preventing ED risk, its application to young climbers remains understudied. This pilot study evaluates the impact of a tailored nutrition education program, NUTYES ("NUTrición Y EScalada": Nutrition and Climbing), on nutritional knowledge and ED risk in competitive youth climbers, providing effect size estimates to inform future definitive trials.